Purification and characterization of a rat liver enzyme that hydrolyzes valaciclovir, the L-valyl ester prodrug of acyclovir - Burnette, T C; Harrington, J A; Reardon, J E; Merrill, B M; de Miranda, P (The Journal of biological chemistry, 1995)
Valaciclovir is an oral prodrug of the antiherpetic agent acyclovir. An enzyme that hydrolyzes valaciclovir to acyclovir, valaciclovir hydrolase (VACVase), was purified from rat liver and characterized. VACVase was a basic (pI 9.4) protein associated with mitochondria. It was monomeric and had a molecular mass of 29 kDa. Amino acid sequences of six VACVase peptides, including its NH2 terminus (13 amino acids) and accounting for approximately 20% of its complete sequence, were not found in the SwissProt protein data base. VACVase hydrolyzed other amino acid esters of acyclovir in addition to valaciclovir (kcat/Km = 58 mM-1 s-1), with a preference for the L-alanyl (kcat/Km = 226 mM-1 s-1) and L-methionyl (kcat/Km = 200 mM-1 s-1) esters. It did not hydrolyze other types of esters or numerous di- and tripeptides and aminoacyl-beta-naphthylamides. Hydrolysis of valaciclovir by VACVase was not inhibited by amastatin, antipain, aprotinin, bestatin, chymostatin, E-64, EDTA, ebelactone A, ebelactone B, elastatinal, leupeptin, pepstatin, or phosphoramidon. It was neither inhibited nor activated by Ca2+, Co2+, Mg2+, Mn2+, or Zn2+. Therefore, this enzyme is not a typical esterase or peptidase and, to our knowledge, it has not been described previously. Its physiological function is not known; however, it may play a significant role in the biotransformation of valaciclovir to acyclovir.